IRRADIATION TEST OF SURROGATED PWR FUEL PIN DESIGN MANUFACTURED WITH nUO2 - Suwardi . (Urania : Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2014)
ABSTRACT PREDICTION OF DIAMETRICAL BEHAVIOR ON PRELIMINARY IRRADIATION TEST OF SURROGATED PWR FUEL PIN DESIGN MANUFACTURED WITH NATURAL UO2. A prototype of fuel pin design for Pressurized Water Reactor (PWR) has been manufactured in the Experimental Fuel Element Installation (EFEI) at Serpong. Power ramp test facility (PRTF) has been revitalized for testing the prototype performance during power ramp. Base-load irradiation of prototype-2 has been done by simulated power in PRTF. The pertinent parameter of pre-ramp irradiation is pellet and cladding dimensional change up to the point of pellet cladding mechanical interaction (PCMI). Slow ramp power mode has been chosen because the evaluated pin consists of natural uranium pellets. The result shows that dimensional change of pellet and cladding resulting from thermal, mechanical and chemical effect of irradiation occurs until depletion of 235U by burnup below depletion in commercial U enrichment. The maximum fuel temperature is < 60oC, while minimum gap attained 17% of its initial value. It is concluded that the available power inside the PRTF capsule is still below the requirement for fuel pin test. With reference of measured power distribution of RSG-G.A.S. core 83 near PRTF, the author recommends re-evaluating the available flux data inside PRTF capsule to determine if a second simulation is needed. Keywords: modeling, PWR fuel, geometry, mechanical interaction.   ABSTRAK PREDIKSI PERILAKU DIAMETER BATANG PADA UJI IRADIASI PENDAHULUAN DESAIN PIN BAHAN BAKAR PWR DIBUAT DENGAN DENGAN BAHAN UO2 ALAM. Sebuah prototipe desain pin bahan bakar untuk Reaktor Air Tekan (PWR) telah diproduksi di Instalasi Elemen Bakar Eksperimental (EFEI) di Serpong. Fasilitas uji daya naik (PRTF) telah direvitalisasi untuk menguji kinerja prototipe selama daya naik. Iradiasi beban dasar dari prototipe-2 telah disimulasikan dengan menggunakan daya sesuai data PRTF. Parameter penting pada iradiasi daya naik adalah perubahan dimensi pelet dan cladding hingga terjadi interaksi mekanik pelet kelongsong (PCMI). Kenaikan lambat daya telah dipilih karena pin dievaluasi terdiri dari pelet uranium alam. Hasil menunjukkan perubahan dimensi pelet dan cladding yang dihasilkan dari efek termal, mekanik dan kimia iradiasi sampai menipisnya 235U dengan fraksi bakar di bawah deplesi pada pengayaan U komersial. Temperatur bahan bakar maksimal <600 oC, sedangkan gap minimum mencapai 17% dari nilai awalnya. Dapat disimpulkan bahwa daya yang tersedia di dalam kapsul PRTF masih dibawah keperluan untuk uji pin bahan bakar . Dengan referensi distribusi daya RSG-GAS terukur pada teras 83 dekat PRTF, penulis merekomendasikan untuk mengevaluasi kembali data fluks tersedia di dalam kapsul PRTF, kwmudian menentukan apakah simulasi kedua diperlukan. Kata kunci: pemodelan, bahan bakar PWR, geometri, interaksi mekanik.